Effects of aqueous extract of Fadogia agrestis stem in alloxan-induced diabetic rats (Bangladesh Journal of Pharmacology, 2014)
Aqueous extract of Fadogia agrestis stem at the doses of 18, 36, and 72 mg/kg body weight was investigated for antidiabetic activity in alloxan-induced diabetic rats. The results revealed that the administration of alloxan significantly increased (p